Experimental study on combustion and emissions of an SI engine with gasoline port injection and acetone-butanol-ethanol (ABE) direct injection. (15th January 2021) - Guo, Zezhou; Yu, Xiumin; Sang, Tao; Chen, Zhao; Cui, Shike; Xu, Mingjia; Yu, Longlong
Highlights: High ratio and early direct injection timing (DIT) of ABE can obtain higher IMEP. GPI + ABEDI can reduce CoVIMEP and CA0-90 especially at lean burn condition. Late DIT can effectively reduce NOx while early DIT is beneficial for lower HC. 40% or 60% of ABEDIr with early DIT can effectively reduce the particle number. 80% of ABEDIr combined with DIT = 300° CA BTDC can be regarded as best condition. Abstract: Using ABE instead of bio-butanol as an alternative fuel can reduce the costs of separating and purifying bio-butanol from ABE solution. This paper investigated the performance of an SI engine with gasoline port injection plus ABE direct injection (GPI + ABEDI) at different ABE direct injection ratio (ABEDIr), excess air ratio (λ) and DIT. Results show that, with increasing ABEDIr, IMEP basically increases continuously at λ = 0.9 while increases firstly and then decreases at λ = 1.0 to 1.3. The highest IMEP is 7.3%, 5.2%, 3%, 2.8% and 3.7% higher than that of gasoline at λ = 0.9 to 1.3. CA0-10, CA0-90 and CoVIMEP with ABE addition are lower than that of gasoline, and minimum CA0-90 value is 6.9%, 11.2% and 18% lower than that of gasoline at λ = 0.9, 1.0 and 1.3. HC emissions decrease initially and then increase as ABEDIr increases, and ABEDIr and DITs corresponding to lowest HC emissions are concentrated at 20%, 40%, 60% and 300-210° CA BTDC, respectively. NOx emissions of 75° CA BTDC are the lowest while pure ABE with early DIT owns lower CO. Nucleation mode, accumulation mode and total particle number (TPN) decrease initially and then increase as ABEDIr increases. 40% or 60% of ABEDIr with 300 and 255° CA BTDC of DIT are superior for lowest particle number (PN), and the lowest TPN is 99.9%, 99.9%, 99.6%, 96.6% and 90% lower than that of gasoline at λ = 0.9 to 1.3, respectively. In summary, GPI + ABEDI mode adopting 80% of ABEDIr combined with DIT = 300° CA BTDC can effectively improve combustion and emissions.